GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 1256071 species occurrences available in GBIF matching the query: TaxonKey: Hemiptera Linnaeus, 1758 HasCoordinate: true HasGeospatialIssue: false. The dataset includes 1256071 records from 871 constituent datasets: 10 records from Stadtpark Herzberg (Elster). 3 records from Alter Kreidebruch Saßnitz/Rügen. 3 records from Rund um das LUGY. 1 records from Landschaftsschutzgebiet Buchhorst 3. 3 records from Stever. 2 records from Wassermann. 2 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 2 records from Kohlbach (Sulzfeld). 6 records from Schulzentrum "Parc Hosingen". 3 records from Schulgarten Zinnowwald-GS. 2 records from Dornwanger Moos. 12 records from Die Teiche im Britzer Garten. 10 records from Butterberg, Dardesheim. 1 records from Nationalpark Jasmund. 7 records from Bulau. 1 records from Werl macht sich auf die Suche. 3 records from Rur. 2 records from Parkuntersuchung Weißer See. 5 records from Feuchtbiotop Weidenkaule. 2 records from Wälder bei Nordkirchen. 5 records from Naturpark Kottenforst-Ville 19.6.09. 2 records from Liether Park (LMS), 5a. 1659 records from Auchenorhyncha collections of SW Finland. 11213 records from Heteroptera collections of SW Finland. 2530 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 77 records from OEH Atlas of NSW Wildlife. 710 records from Insect Collection (CeStuBio). 1288 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 247 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 45 records from Australian National Wildlife Collection provider for OZCAM. 298 records from dec2011. 243 records from AntWeb. 19787 records from CAS Entomology (ENT). 170 records from PlutoF platform observations. 7264 records from NHM, Heteroptera. 2135 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 16905 records from Cicadelidos (Hemiptera: Cicadellidae) de Colección Entomológica del Instituto Alexander von Humboldt. 7 records from Merseyside BioBank - North Merseyside Insects (verified). 102 records from Inventario Español de Especies Terrestres (MAGRAMA). 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 3 records from BTCV Scotland - BTCV wildlife counts recording workshops. 839 records from NINA Vanndata øvrige arter. 1904 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - Flickr (01) Shieldbugs & allied species. 100 records from Royal Horticultural Society - Nezara viridula records held by the Royal Horticultural Society. 3413 records from Alterra (NL) - Entomofauna inventory in peat swamps. 8 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 217 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 214 records from Collection of Heteroptera. 7 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 1 records from Zoology (Museum of Evolution - Uppsala). 205 records from EPA River Biologists data. 3083 records from Finnish Entomological Database: Heteroptera. 2 records from Local BioBlitz Challenge 2013. 9301 records from Highland Biological Recording Group - HBRG Insects Dataset. 2144 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 366 records from Lyman Entomological Museum (LEMQ). 8 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 4 records from Clare Biological Records Centre dataset. 52 records from Monitoring data from the federal state Bavaria (Germany). 358 records from Royal Horticultural Society - Records from the RHS insect reference collection. 55 records from NINA insect database. 17 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 151061 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 5 records from Plants galls. 2125 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 4673 records from Museum Victoria provider for OZCAM. 12 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 88 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 2 records from Chrysomelidae of the Carpathians. 522 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 3244 records from Museum of Comparative Zoology, Harvard University. 2321 records from AM: Freshwater Invertebrates (1900-2005). 3771 records from BioFokus. 5 records from Bioblitz 2013 Copenhagen Denmark. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 65603 records from Artdata. 12 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 10516 records from Danish Plant Bugs (Miridae). 67 records from Various insect orders, NEF. 159052 records from Especímenes INBio. 399 records from Données ONF Faune-Flore-Fonge. 12 records from arim. 46 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 5529 records from Hemipteran specimens of Iwate Prefectural Museum. 1583 records from Estonian Museum of Natural History. 6064 records from NMNH occurrence DwC-A. 1 records from Im Bauerngarten. 2 records from Klasse 3a. 4 records from Kremmer Luch. 1 records from LauWi. 3 records from Ehmkendorf. 2 records from Fledermaus. 3 records from Feriendorf des Kreises Gedern (Ober-Seemen). 3 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 2 records from Naturgrundstück (Eutin). 7 records from Truppenübungsplatz Panzerkaserne Böblingen. 5 records from Föhrenried (Fronreute und Baindt). 5 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 2 records from Triebesbach (Zeulenroda-Triebes). 1 records from Dellwiger Bach (Dortmund). 1 records from "Schwarzes Teich" (Waldpark Radebeul). 4 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 1 records from Örtzemündung (Stedden). 2 records from Hainbachtal in Oelsnitz/V.. 2 records from Die Wuhle. 6 records from Wirbach. 4 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 11 records from Paul-Gerhardt-Schule Dassel. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 160 records from Colección Limnológica del Chocó. 64 records from Australia's Virtual Herbarium. 9592 records from Collection of various insect orders, Natural History Museum, University of Oslo. 246 records from Colección Limnológica Universidad de Antioquia. 1 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 190 records from Tasmanian Museum and Art Gallery provider for OZCAM. 298 records from Monitoring data from the federal state Hesse (Germany). 400 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 2244 records from Recent Invertebrates Specimens. 10862 records from Heteroptera of Ireland. 1 records from Invertebrates Collection of the Swedish Museum of Natural History. 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 28996 records from mel. 2080 records from Estonian University of Life Sciences. 16496 records from Essig Museum of Entomology. 116 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 968 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 3 records from Seewasen. 3 records from Borkhart. 6 records from Küstenschutzwald. 1 records from Waldsee. 3 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 1 records from Biotop "Kohlbeke" (Berlin-Marzahn). 1 records from Heidesee / Halle. 4 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 9 records from Kiesgruben Wemb. 2 records from Artenvielfalt Kreis Gießen. 57 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 5575 records from iNaturalist research-grade observations. 12 records from Upper Silesian Museum, Bird Observations. 73 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 191 records from Monitoring data from the federal state Saxony (Germany). 5 records from Feriendorf Ober-Seemen. 2 records from Fuchsloch (Mohlsdorf/Ostthüringen). 1 records from Schulgarten mit Klasse 8a (Essen). 1 records from Roter Berg Werdau (Leubnitz). 6 records from Regenrückhaltebecken (Zeulenroda). 6 records from Deponie Klausdorf. 1 records from Südpark (Bochum-Wattenscheid). 1 records from Kabelskebach (Kabelsketal, Saalkreis). 3 records from verschiedene Kleingewässer um Oldenburg/Holstein. 5 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 3 records from Schussenaue bei Berg. 3 records from Ried und Sand - Artenvielfalt durch Beweidung. 1 records from Junge Heide, Radebeul/Dresden. 1 records from Insektenvielfalt Ahe/Weichelsee. 4 records from Schulgarten Hans-Carossa-Oberschule. 2 records from Erft in Selikum (Neuss). 1 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 1 records from Trockenrasen bei Dörndorf. 1 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 5 records from Garten J. Scherrer (Lachen-Speyerdorf). 7 records from Tag der Artenvielfalt BUND Kaiserslautern. 4 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 4 records from Schafsweide Seniorenhaus Berghof. 4 records from Höltigbaum. 4 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 1 records from Waldstück Bremerhagen LK Bio Kl. 12. 7 records from Steinbruch Mainz-Weisenau, 3. Jahr. 5 records from Biosphäre Bliesgau. 1 records from Wulfsmuehle/Pinnau. 1 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 2 records from Bad Bodenteicher Heide. 1 records from Selz (Ingelheim am Rhein). 6 records from Schulgarten Fichteschule. 590 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 2 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 70 records from Census of the animals of Benin. 1 records from Siegen/ Gymnasium Am Löhrtor. 1 records from Förderzentrum Schmölln. 5 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 3 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 2 records from Wiese am Unterbecken. 1 records from Wangerooge. 6 records from Umgebung der Grundschule Oderberg. 52 records from Zentralfriedhof (Wien). 4 records from Spießwoogtal / Königsbruch (Fischbach). 2 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 2 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 2 records from Grillhütte Wettsaasen, Wiese, Hecken. 7 records from Gelände des Schulzentrums am Himmelsbarg. 3 records from Industriebrache (Kempen). 1 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 4 records from Römertal (Steinpleis). 1 records from Mittelriede Höhe Gliesmarode-Braunschweig. 4 records from Schulgelände Ceciliengymnasium. 3 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 2 records from Olympiapark (München). 1 records from Lahnufer in Villmar. 1 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 8 records from LBV-Kindergruppen Markt Tussenhausen. 2 records from Kleinstbiotop mit Schulteich/Weißwasser. 1 records from Bachpatenschaft Beeke. 1 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 1 records from LSG Saale, Rößewiesen (Bernburg/Saale). 16 records from Waldi-Weiher. 3 records from Landschaftsschutzgebiet Schmutterwald. 5 records from Kaniswall/ Gosener Wiesen an der Spree. 4 records from Bernhardsthal. 4 records from Tornoer Teich. 2 records from Aachtobel. 4 records from Steinbruch Kronungen. 6 records from FFH-Gebiet Paartal. 6 records from Schulgarten Janusz-Korczak-Realschule. 1 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 3 records from Art´n Vielfalt im Kinderwald. 2 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 6 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 5 records from Steinbruch Mainz-Weisenau. 14 records from Steinbruch Mainz-Weisenau, 2. Jahr. 1 records from GymnQuerfurt. 1 records from Rund ums Ökohaus (Würzburg). 2 records from Schulhof Sandhofenschule (Mannheim). 4 records from Artenvielfalt im Beckerbruch (Dessau). 1 records from Trockenrasen Franzigmark (Halle/Saale). 3 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 2 records from Mauernacker (Wettsaasen). 6 records from Umgebung des Spalatin Gymnasium Altenburg. 7 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 1 records from Amtsrain Apolda-Zottelstedt. 2 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 1 records from WildesMoor bei Schwabstedt. 12 records from Binsenwiesen. 4 records from Isartal Dingolfing. 3 records from Birkenloh. 1 records from GE-Brühl. 1 records from Neanderthal. 2 records from Regenwasserabfangsbecken (Erlenbach). 2 records from NABUGEO1. 3 records from Landschaftspark St.Leonhard-Deisendorf. 3 records from Wiese Niederaula. 2 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 1 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 1 records from Naturschutzgebiet Kochertgraben. 4 records from Issumer Fleuth. 1 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 2 records from Glemstal (Leonberg). 3 records from Tümpel Schulbiologiezentrum. 1 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 52 records from IBF Monitoring of Plant Galls. 1 records from Tiere. 2 records from Schulgelände Paul-Gerhardt-Schule. 114 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 5 records from Bannwald Burghauser Forst. 4 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 8 records from Rohrmeistereiplateau und angrenzendes Gebiet. 4 records from Fürstenberger Ralley Teil 3. 6 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 2 records from Haarbach Höfe. 3 records from Gewässeruntersuchung Grötzinger Baggersee. 1 records from Landschaftsschutzgebiet "Holmer Sandberge". 2 records from Mainufer. 3 records from Brander Wald (Stolberg). 1 records from Wasserwerkspark (Chemnitz). 2 records from Düne am Ulvenberg (Darmstadt). 7 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 3 records from Ökologischer Weinberg (Guntersblum). 4 records from Schwanseepark (87645 Schwangau). 4 records from Wirbach-Taubental (Bad Blankenburg). 2 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 7 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 1 records from Dorfrand Mauderode. 1 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 1 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 3 records from Selztal bei Friesenheim. 1 records from Uferzone Wipper (Biesenrode). 1 records from NSG Leist bei Ziegenhain. 1 records from Gieselbachtal Fulda-Harmerz. 3 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 2 records from Weidewirtschaft. 5 records from Kochertgraben II. 3 records from Dalbekschlucht. 12 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 9 records from Leben im Finkensteiner Moor. 1 records from Zoo Frankfurt. 4 records from Kinderbauernhof Pinke-Panke. 4 records from LSG "Großes Bruch". 3 records from 8c. 1 records from Steinbachtal (Würzburg). 5 records from Schulhof A.-Lindgren-Schule (Elmshorn). 1 records from Klütwald. 4 records from Regenrückhaltebecken Bad Bevensen. 2 records from Ökowerk Emden. 1 records from Mühlenbach bei Buxtehude. 3 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 6 records from Estetal (Buxtehude). 3 records from Schulteich Heinrich-Mann-Schule. 8 records from Sudeniederung (Amt Neuhaus). 3 records from Heider Bergsee (Brühl). 1 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 1 records from Wiese hinter der Schule (Darmstadt). 2 records from Kinderwald Hannover. 1 records from Feuchtwiese. 1 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 3 records from Bach. 2 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 2 records from Garten in Schmölln. 5 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 6 records from Plöwener Wald. 4 records from Regenwasserabfangbecken. 5 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 2 records from Schafheide im Böblinger Wald. 2 records from Hoher Stein Kallenhardt. 3 records from Schulgarten-St.-Georg-Gymnasium. 1 records from Schulgelände Lise Meitner Realschule (Paderborn). 3 records from Schulhof A.-Schweitzer Schule (Wetzlar). 1 records from Im und um das Schulhaus. 4 records from Bäche im Mooswald (Vörstetten). 1 records from Kirchheller Heide ( Bottrop). 1 records from Ohemoor (Hamburg/Norderstedt). 2 records from Urwald 2 (Bad Waldsee). 2 records from Landschaftsschutzgebiet Buchhorst 4. 1 records from Rotes Steigle (Panzerübungplatz Böblingen). 2 records from Tiere und Pflanzen am Pfannenbach. 2 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 3 records from Kühnauer Aue und Kühnauer See. 5 records from Naturschutzstation Weinberghaus (Dessau). 3 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 3 records from Weinberg Reichersdorf. 762 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 2 records from Wiesen am Treffpunkt Freizeit. 9 records from Gronau - auf der Suche nach dem Neunauge. 3 records from Streuobstwiese Stedar. 1 records from "Ahrschleife bei Altenahr". 277 records from Colección de Entomología - Auchenorrhyncha. 1 records from BUND Naturschutzzentrum St. Julian. 2 records from Leben auf einer Sturmfläche. 5 records from Vergleich der Fauna eines naturbelassenen mit einem wasserwirtschaftlich veränderten Gewässer. 54802 records from Illinois Natural History Survey Insect Collection. 12209 records from naturgucker. 297 records from National Trust - Hatfield Forest species data held by The National Trust.. 4 records from Baggerseen bei Krauchenwies. 1 records from LBV 100 - Artenvielfalt am Rothsee. 7 records from Biotope in Rheine - Aktion 350. 4 records from Schulteich Freie Waldorfschule Darmstadt. 2 records from Blankenfelder See. 2 records from Müritz-Nationalpark. 3 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 1 records from Expedition "Schulgelände". 4 records from LK 11 im Mönchspark. 3 records from Schulwald Marksuhl. 6 records from FFH-Gebiet Klosterwasser/Burkau. 2 records from Königsdorfer Wald. 123 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 6 records from Liether Kalkgrube. 1 records from Bodenteicher Seewiesen. 2 records from Rund um den Hainbergsee. 3 records from Wir erkunden die Hofau, Klasse 5c. 2 records from Waldwiese. 1 records from Von der Nutzung zur Natur. 1 records from Liether Park 1 (LMS), Klasse 5b. 5 records from BIRDRACE Die TUErteltauben. 2 records from Unter hellen Zinnen und finsteren Grotten. 2 records from Düpenauwiesen. 1 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 1 records from Rosarium (LMS), Klasse 6a. 3 records from Rechts des Inn Höhe Hofau Rosenheim. 2 records from Riekdahler Wiesen. 3 records from Nachtinsekten am Muldenufer. 454 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. 61 records from Biodiversity records from Ireland - general. 55 records from Ireland's BioBlitz 2012. 17 records from Colección Entomológica de la Universidad Tecnológica del Chocó. 1060 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 54 records from The Distribution Atlas of Butterflies in Poland. 5 records from Freiburger GEO-Tag der Artenvielfalt. 21 records from GEO-Hauptveranstaltung in "Wildtierland". 5 records from Schulgelände des Schulzentrums am Himmelsbarg. 3 records from Artenvielfalt in der Kinderakademie im RFZ. 9 records from Mangfalltal. 2 records from GEO-Tag am Hohlen Stein. 1 records from Aktion des Romain-Rolland-Gymnasiums. 8 records from Von Elf bis Elf" Der Botanische Garten Wuppertal. 7 records from Naturschutzgebiet Börstig bei Hallstadt. 1 records from Tag der Artenvielfalt in Heidelberg. 1 records from Tongrube bei Hettstedt. 7 records from NSG Forst Zinna-Jüterbog-Keilberg. 5 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 1 records from Lebensraum Dorf. 6 records from Schulgarten der Volksschule. 2 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 1 records from Wälder im Hainbachtal. 4 records from Ober-Olmer Wald. 4 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 17 records from Schulgelände Grolland. 1 records from Reusaer Wald. 3 records from Feuchtwiese Grüne Mitte, Klasse 5a. 4 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 1990 records from Merseyside BioBank - North Merseyside Insects (unverified). 17 records from BioAcoustica: Wildlife Sounds Database. 3019 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 18 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 7013 records from Entomological collections, UiB. 24 records from Scottish Environment Protection Agency - Scottish river macro-invertebrate records from 2007 collected by SEPA. 52 records from Biosphärenpark Wienerwald - Pfaffstätten. 2 records from Schulaktion des Dienzenhofer-Gymnasiums. 1 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 8 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 2 records from Aktion - Friedensburg Oberschule. 4 records from Artenvielfalt im Rhein-Neckar-Raum. 93 records from Schatzinsel Norderney. 1 records from Naturpark Kottenforst-Ville 15.6.09. 3 records from Streuobstwiese Stedar 2008. 2 records from Schulhofuntersuchung Thomas-Mann-OS. 1 records from Stadtwald Heide. 1 records from Naturpark Kottenforst-Ville 17.6.09. 5 records from Raus in die Natur. 4 records from Rund ums Schulgelände. 7 records from NABU-Fläche am Bösselhausener Weg. 1 records from Seeufer ehem. BUGA-Gelände. 4 records from Leben in den Elbwiesen. 80 records from MfN - Fossil invertebrates Ia. 18 records from Polish seed gene bank – historical passport data of accessions. 406 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 22217 records from Biodiversity Institute of Ontario (BIOUG). 5 records from Sahrbachtal Kreis Ahrweiler. 1 records from Schriesheimer Steinbruch. 29 records from Koleopterologen am Bausenberg. 4 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 9 records from Luderbusch. 1 records from Schulgarten Zinnowwald-Grundschule. 2 records from Mönchspark. 2 records from Feuchtwiese in Langes Tannen (LMS), Klasse 5c. 6 records from Binsenwiesen im Bizzenbachtal. 10 records from Wiesen in der Grünen Mitte. 1 records from Bayerische Donau - Riedlingen. 2 records from "Schule am Inselsee" Güstrow. 1 records from Regenwasserabfangbecken Erlenbach. 1 records from Sukzession Industriebrache. 1 records from Landwehrbach. 40 records from Bumblebees, cuckoobees and butterflies in southern Poland. 1170 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 883 records from KNWR Entomology Collection. 34 records from Ringing Data from the Bird Migration Research Station, University of Gdańsk. 5765 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 4 records from NODC WOD01 Plankton Database. 180 records from Database on Forest Disturbances in Europe. 250 records from IndOBIS, Indian Ocean Node of OBIS. 4 records from Coleção Entomológica Paulo Nogueira-Neto - IB/USP. 43 records from Danielsberg (Mölltal, Kärnten). 53 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 7 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 3 records from Zukünftiges NSG Höftland/Bockholmwik. 1 records from Freiburger Tag der Artenvielfalt. 5 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 4 records from Schulgarten Huttenheim (Philippsburg/Baden). 12 records from Philosophenwald und Wieseckaue in Gießen. 3 records from Bayerische Donau - Blindheim Donaubrücke. 3 records from Schiller Gymnasium Hof 10b. 2 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 2 records from Lebensraum Walram. 1 records from Artenvielfalt des "Grünen Klassenzimmers". 2 records from Listhof und Umgebung. 2 records from Naturpark Kottenforst-Ville 16.6.09. 3 records from Naturnachmittag 'Artenvielfalt an der Ecke' (Wäldchen an der Wegegabelung). 1 records from Exkursion Ebertsheimer/Grünstädter Berg. 1 records from Artenvielfalt und Kulturlandschaft. 2 records from Feuerlöschteich, Wald und Dünen in den Holmer Sandbergen. 4015 records from Tullie House Museum - Tullie House Museum Natural History Collections.. 68 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 113 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 2 records from Artenvielfalt rund um die Dalbek-Schule. 4 records from Schulgarten Am Hafen. 8763 records from IZIKO South Africa Museum Hymenoptera Collection (1800-2013). 1 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 5 records from SysTax - Zoological Collections. 189 records from Macaulay Library Audio and Video Collection. 2 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 43 records from RBINS collections. 7 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 34544 records from Aquatic Heteroptera Recording Scheme - Aquatic Heteroptera Dataset. 5 records from Collection Hemiptera - SNSD. 2608 records from Swiss Psyllid (Hemiptera) Collections - Basel. 1 records from HMAP-History pf Marine Animal Populations (CoML). 4 records from Atlantic Reference Centre (OBIS Canada). 6 records from Stausee (Oberdigisheim/Meßstetten). 1 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 4 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 5 records from Bonner Schülerinnen am Rodder Maar. 4846 records from Heteroptera. 27716 records from Insekten Sachsen. 856 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 5 records from Lichen herbarium, Oslo (O). 8 records from Insect Specimens deposited in the Saga Pref., Space and Science museum, JAPAN. 3 records from Familientag am Schorberg. 1 records from Feuchtbiotop Otto-Hahn-Gymnasium. 4 records from Fluss - Vielfalt. 5 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 2 records from Wasserbachsee. 166 records from Missouri Botanical Garden. 766 records from Natural History Museum (London) Collection Specimens. 2090 records from Insect Collection of Saitama Museum of Natural History. 7 records from Harold W. Manter Laboratory of Parasitology Collection. 14 records from EPA'S EMAP Database. 3 records from NBI. 1 records from Plants of Papua New Guinea. 16 records from Laboratório de Ecologia e Biogeografia de Insetos da Caatinga. 1 records from MAL. 477 records from Staffordshire Ecological Record - SER Site-based Surveys. 1 records from Repatriación de datos del Herbario de Arizona (ARIZ). 1056 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 568 records from University of Alberta Entomology Collection (UASM). 5 records from LaBoOb02. 3 records from DJH. 1 records from AKG-Gelände (Bensheim). 3 records from Artenvielfalt auf den Elbwiesen (Dessau). 3 records from Schlichemquelle (Tieringen/Meßstetten). 19 records from Gemeinde Sursee. 65 records from Naturschutzgebiet Bausenberg. 2 records from Altholzparzelle Eilenriede Hannover. 3 records from Schlern - (Bozen). 58 records from GEO Hauptveranstaltung Tirol (Innsbruck). 8 records from Königstetten. 1 records from Frauenholz (Holzmaden). 903 records from Open Mosaic Habitat Survey Group - Invertebrates recorded during Open Mosaic Habitat survey in England and Wales (2012). 7 records from North Ayrshire Countryside Ranger Service - Species within North Ayrshire from 1984 - Present. 24 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 90 records from BioBlitz Barcelona 2010-14. 667 records from Northern Territory Museum and Art Gallery provider for OZCAM. 2737 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 25 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 61 records from Akita Prefectural Museum, Insect Collection. 1 records from Bayerische Donau - Tapfheim. 1 records from 2. Aspacher GEO-Tag der Artenvielfalt. 1 records from Fliegenhaupt Marksuhl. 5 records from Grundschüler erkunden Schulumgebung. 6 records from Grünes Germersheim. 2 records from Ober-Olmer Wald 09. 1 records from Schulteich Regionales Förderzentrum "J.H. Pestalozzi" Sondershausen. 3 records from Schulwald Sprendlingen. 1 records from Wasser-Lernort Nettemündung. 1 records from Wuhle - Brücke/ Mosbacher Straße. 3 records from Collection Crustacea - ZMB. 2185 records from Naturhistorisches Museum Mainz, Zoological Collection. 516 records from Lothian Wildlife Information Centre - Lothian Wildlife Information Centre Secret Garden Survey. 10322 records from UAM Insect Collection (Arctos). 231 records from Ireland's BioBlitz. 820 records from Ibaraki Nature Museum, Arthropoda collection. 1 records from Tartu University, palaeontology collections. 1 records from Collection Insecta fossil - SMF. 1 records from Laboratorio de Entomología y Control de Plagas del Instituto Cavanilles de Biodiversidad y Biología Evolutiva de la Universidad de Valencia: ENV. 1 records from Southampton Oceanography Center Discovery Collections Midwater Database. 146 records from Paleobiology Database. 66 records from Individual Sightings. 19 records from Arctic Ocean Diversity. 1 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 9 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 85 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo Páramos Chilí - Barragán, Tolima. 37806 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 6 records from Priest Pot species list, Cumbria, Britain. 19108 records from Danish waterbugs (Insecta: Hemiptera-Heteroptera: Gerromorpha + Nepomorpha). 197 records from University of Alberta Museums, Freshwater Invertebrate Collection. 4 records from UNSM Vertebrate Specimens. 2 records from Mariposas (Lepidoptera: Papilionoidea) de la Colección Entomológica del Instituto Alexander von Humboldt. 1661 records from Invertebrate Paleontology Division, Yale Peabody Museum. 2 records from Invertebrate Zoology Division, Yale Peabody Museum. 66 records from GEO Biodiversity Day. 20347 records from Biologiezentrum Linz. 13 records from invertebratezoology. 71 records from Arthropod fauna in christmas tree plantations. 12 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 933 records from Insects specimen database of Osaka Museum of Natural History. 21 records from BÜG. 7 records from Klutensee. 3 records from Am Moosangerweg. 7 records from Streuobstwiese RSG (Cham). 3 records from Botanischer Garten (Saarbrücken). 1 records from Hamberger Brücke / Würmtal (Pforzheim). 2 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 1 records from Sandhofen. 8 records from Mooswald (Freiburg). 4 records from Gewann Krampf (Heilbronn). 4 records from Landschaftspflegehof (Berlin). 5 records from Schulhof Bühlschule Giengen. 6 records from Schule Sulzbach (Oberegg). 4 records from Langes Tannen (Uetersen). 21 records from Gelände des IVL (Zeckern). 9 records from Wald und Wiese am Buchwald. 3 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 5 records from Langes Tannen. 15 records from Observations du Conservatoire botanique national du Bassin parisien.. 1 records from ZFMK Heteroptera collection. 31 records from inatura - Erlebnis Naturschau Dornbirn. 1 records from NCOS1959_Mollusca (OBIS China). 1743 records from Colección de artrópodos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 10 records from Invertebrates compiled by W.Block. 2 records from Überall ist Wunderland. 1 records from Frau Voss. 1 records from Naturschutzstation Schmidsfelden. 6 records from Erzental (Oberotterbach). 15 records from Naturschutzgebiet Bausenberg (Niederzissen). 2 records from NSG Karwendel. 4 records from Umgebung der Gesamtschule Hamburg-Winterhude. 2 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 8 records from GEO-Tag der Artenvielfalt auf dem Bausenberg mit den 4. Klassen der Brohltaler Grundschulen. 1 records from Cuxhavener Küstenheiden. 9 records from Danisco-Wiese. 1 records from katzenbuckel. 1 records from GEO-Hauptveranstaltung (Insel Vilm). 21 records from Unser Schulgelände. 30 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 1 records from Nottekanal, Klasse 7 - 10. 3 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 20 records from Riedensee. 3 records from Überschwemmungsgebiet der Wied. 2 records from 20 Jahre Naturschutzgebiet Dreienberg. 4 records from Schaalbach. 5 records from Pottundkopp. 2 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 3 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 2 records from Biotop Binsenwiesen (Wehrheim/Taunus). 1 records from Streuobstwiese/Naturerlebnisraum Koppelsberg (Plön). 6 records from Schulgelände Schule auf der Aue, Münster. 3 records from Schulbiotop Dr.-Gustav-Schickedanz-Hauptschule (Fürth). 5 records from Unser Schulhof. 1 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 3 records from Streuobstwiese Kugelberg (Ulm). 1 records from Wismar Bucht coast-watching. 3 records from Fuldaaue (Stadtgebiet Fulda). 4 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 3 records from Erlengraben/Lipp-Tal (Östringen). 14 records from Neckartalsüdhang (Horb). 1 records from nazza. 78 records from GEO-Hauptveranstaltung (Duisburg). 11 records from Pilstingermoos. 7 records from Biotope auf dem Gelände der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 2 records from Wald am Schloss Wittgenstein Bad Laasphe. 2 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 8 records from Kiesbagger (Mittelhausen). 1 records from Natur aus zweiter Hand am Muldestausee. 4 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 3 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 10 records from renaturierter Main (Kemmern bei Bamberg). 3 records from Unterbrucker Weiher. 3 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 4 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 8 records from Walldorf-Wiesloch: "Natur über den Gleisen". 5 records from Artenvielfalt im Umfeld der Burgwegschule. 2 records from VSN-Wiese. 22 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 1 records from Natural History Museum, University of Tartu. 9 records from Colección Nacional de Entomología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2785 records from Homoptera. 1 records from Freiburger Netzwerk Artenvielfalt. 124 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 2 records from Klostergarten St Luzen. 1 records from EDIT - ATBI in Gemer area (Slovakia). 3 records from Artenvielfalt am Schlern. 7 records from Collection Mollusca SMF. 7 records from University of Florida Invertebrate Paleontology. 358 records from Scottish Environment Protection Agency - River macroinvertebrate data for 2005 and 2006. 311 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 38 records from Carpatica Operation. 4995 records from Limnodata. 18905 records from Queensland Museum provider for OZCAM. 6688 records from Geographically tagged INSDC sequences. 41 records from Fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 399 records from Données ONF Faune-Flore-FOnge. 1 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 2 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 30 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 1 records from Artenvielfalt auf Restbauernhof. 3 records from Wiese und Weide am Waldrand von Gusterath. 1 records from Umgebung von Schorndorf. 2 records from Promberg1. 3 records from Wanderweg am Windebyer Noor (bei Eckernförde). 12 records from BUND - Dassower See (Lübeck/Dassow). 2 records from Wildes Bremer Leben im Park. 3 records from Schulhof (Bad Waldsee). 14 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 5 records from Luch Niederlehme, Schüler der Klasse 7. 3 records from Stadtbiotop Ulrichteich. 36 records from Heinersdorfer Sumpfwiese. 3 records from Knechtweide (Kohlfurth). 1 records from Industriegebiet (Kempen). 1 records from Ökostation (Freiburg). 3 records from Langes Tannen in Uetersen. 1 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 12 records from NSG Berschau - Auengebiet (Neustadt / Wied). 1 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 1 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 2 records from Schloß Türnich (Kerpen). 2 records from Quarrendorfer Landschaftsschutzgebiet. 2 records from Faberpark (Nürnberg/Stein). 8 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 5 records from Schulprojekt (Bremen). 2 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 3 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 10 records from Schulhof und Anlagensee in Nellingen. 6 records from Tiergarten Straubing. 2 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 4 records from Eppingen und Umgebung. 2 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 6 records from Prophetensee Quickborn. 2 records from Dreilinden Gymnasium-Schulgelände. 3 records from Maschwiesen Laatzen. 6 records from Himmelmoor. 3 records from Altenburg bei Bamberg. 23 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 1 records from KU Museum of Invertebrate Paleontology. 14 records from Blumenrather Heide / Virneburg. 135 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from Biologische Station im Kreis Wesel. 1 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 10 records from Gurgltal (Tarrenz). 2 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 3 records from schulgarten. 8 records from Bergkamen- Bergehalde Großes Holz. 1 records from Küste Wismar-Wendorf bis Hoben. 1 records from Halberg bei Neumorschen. 4 records from Hintere Halde. 1 records from Freiheitsring (Frechen). 6 records from Teich Berlin Wuhlheide. 1 records from Artenvielfalt auf dem Schulgelände. 108 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 2239 records from Derbyshire Biological Records Centre - Hemiptera Records 1969 - 2011. 28 records from New Mexico Biodiversity Collections Consortium database. 2 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 3 records from Kohlstattbrunnental. 936 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 379 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 4227 records from Invertebrate collection of Jyväskylä University Museum. 14 records from Herbier de la Guyane. 27 records from Wetland Inventory (NV). 56 records from Alterra (NL) - Entomofauna inventory in edges of arable fields province of Groningen. 2 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 14 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 9100 records from Australian National Insect Collection. 742 records from A geographic distribution database of the cassava whitefly complex (Hemiptera, Aleyrodidae) and their associated parasitoids and hyperparasitoids (Hymenoptera). 361 records from RSPB - Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. RSPB led project with 50% funding from Natural Engl. 100 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 29 records from Anymals+plants - Citizen Science Data. 6 records from Stadt Königs Wusterhausen. 1 records from Stadtpark Sulzbach-Rosenberg. 9 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 5 records from Bizzenbachtal (Wehrheim/Taunus). 7 records from Werremündung im Schwarzatal. 2 records from Steinbruch Haas Stuttgart-Münster. 9 records from Weidenhüttendorf an der Würm (München). 2 records from Kühnauer See (Dessau). 5 records from Lebensraum Stadt und Park. 3 records from Wupperaue bei Kemna (Wuppertal). 2 records from An der Ohm, (Wettsaasen). 3 records from Spandau HBO. 2 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 80 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 5 records from Mißmahlsche Anlage. 6 records from Naturgarten Langenholtensen. 1 records from Arteninventar rund um den Rannahof. 5 records from Unna-Mühlhausen, Wiesen. 10580 records from Natural England - Invertebrate Site Register - England.. 44 records from Royal Horticultural Society - Pittosporum sucker (Trioza vitreoradiata) records acquired by the Royal Horticultural Society. 9 records from Polish gene bank – passport data of plants accessions which are important in human life. 5 records from Coleccion de sonidos ambientales. 3 records from Rössewiesen am Krumbholz. 9 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 80 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 3 records from Biosphärenreservat Münsinger Alb. 1 records from Waldstück am Schullandheim Bad Bederkesa. 2 records from Kaulsdorf. 5 records from Auenwiesen und Trockenrasen. 1 records from Waldwandel in Monschau-Mützenich-Boverei. 366 records from Gunma Museum of Natural History, Insect Specimen. 887 records from Fiji Terrestrial Arthropods. 6 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 20 records from Biological Records Centre - RISC Non-Native Species Records for Rhododendron Leafhopper. 1155 records from Colección del Departamento de Biología Animal (Zoología) de la Universidad de La Laguna. 50696 records from Biological and palaeontological collection and observation data MNHNL. 745 records from Entomology Division, Yale Peabody Museum. 1097 records from UAM Insect Observations (Arctos). 283 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 4 records from Perchtoldsdorfer Heide. 6 records from Tag der Artenvielfalt mit SchülerInnen des Leibniz-Gymnasiums in Neustadt a.d.W.. 5 records from Ostfriesland. 1 records from Flora und Fauna in unserer Kita. 7 records from Lustadter Wald .. 1 records from Gymnicher Mühle. 1 records from Therevid PEET Project. 2270 records from Insect Collection of Natural History Museum and Institute, Chiba. 14806 records from Texas A&M University Insect Collection. 1 records from Tag der Artenvielfalt im Taubental. 76 records from Monitoring data from the federal state Berlin (Germany). 82 records from National Trust - Sutton Hoo species data held by The National Trust.. 16 records from IITA Cameroon Insect. 38 records from National System of Protected Areas in Poland - Plants. 97 records from ArtenFinder. 142 records from National Trust - Ickworth species data held by The National Trust.. 807 records from Fieldjournal.org observation database. 263 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - RISC Heteroptera Non-Native Species Records. 7055 records from Environment Agency - Environment Agency freshwater invertebrate species (single species families). 662 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 62 records from Wildlife Sightings. 1348 records from Insect Collection of Taiwan Forestry Research Institute. 369 records from European Molecular Biology Laboratory Australian Mirror. 261 records from Instituto de Ciencias Naturales. 109 records from Seil Natural History Group - SNHG Biological Records Dataset. 952 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 782 records from Colección de Entomología - Heteroptera. 7084 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 222 records from Colección de artrópodos del PNN Gorgona - Museo de Entomología de la Universidad del Valle (MUSENUV). 506 records from Queen Victoria Museum Art Gallery provider for OZCAM. 8335 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Invertebrate Observation Records other than Lepidoptera. Pre-2010 for Cumbria. 2 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 33 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 1 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 45285 records from Biological Records Centre - Water Bug (aquatic Heteroptera) data for Britain. 1 records from First record of Eggplant Mealybug, Coccidohystrix insolita (Hemiptera: Pseudococcidae), on Guam: Potentially a major pest. 29096 records from Snow Entomological Museum Collection. 4404 records from Norwegian Species Observation Service. 8 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 1 records from Herbier_CNSF. 12 records from Animal Sound Archive. 4008 records from Pond Conservation - National Pond Monitoring Network collated pond survey data for Great Britain 1972 to 2007. 163 records from Staffordshire Ecological Record - SER Species-based Surveys. 317 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - iSpot (2008-2010): Shieldbugs & allied species. 2685 records from CU Invertebrate Paleontology. 3614 records from UCMC_Entomology. 936 records from University of Ghana - Ghana Herbarium, Insects collection. 26 records from Estonian Nature Observations Database. 19 records from Carabidae of the Carpathians. 10 records from Countryside Council for Wales - Freshwater Site Visits. 8282 records from Inventaire National du Patrimoine Naturel : Insectes Hétéroptères Mirides de France. 3166 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 59 records from Nijmegen Natural History Museum (NL) - Entomological Collection. 90 records from Entomology at ZMUC, Natural History Musem of Denmark. 237 records from Littoral Macroinvertebrate data from Irish lakes. 20 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 116 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 112 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 17 records from Colección Entomológica CDMB. 5092 records from MUST, Insecta. 2 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 3 records from National System of Protected Areas in Poland - Animals. 35999 records from Australian Museum provider for OZCAM. 835 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 1 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 487 records from Occurrences in SinBIOTA. 4168 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 3569 records from Nottinghamshire Biological and Geological Records Centre - UK abstract from Nottingham City Museums & Galleries (NCMG) Insect Collection Baseline database. 4480 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 312 records from Natural History Museum Rotterdam (NL) - Insecta collection. 1846 records from Alterra (NL) - Entomofauna inventory in riverside grasslands. 103 records from Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1048 records from Alterra (NL) - Comparison of entomofauna in four different habitats. 1 records from Miscellaneous Vascular Plants. 86 records from National Trust - Heigham Holmes species data held by The National Trust. 455 records from BioFresh Pond Data. 83 records from New distributional data on aquatic and semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha & Nepomorpha) from South America. 259 records from Macroinvertebrate abundance in river biotopes across England and Wales. 25 records from Arthropod collection, Tromsø Museum. 144 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 9094 records from Countryside Council for Wales - Welsh Peatland Invertebrate Survey (WPIS). 5360 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 1 records from National Museum of Natural Science. 1570 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2007 - Mammal Survey Estonia. 770 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 88 records from Northern Ireland Environment Agency - EHS Species Datasets. 3 records from Macroinvertebrate abundance in montane tropical streams of varying land-use, Ecuador. 2 records from Cryptogamy collection (PC) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 20247 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups.
Keywords: GBIF; biodiversity; species occurrences